Association of hyperlipidemia in preterm delivery - Sowmiya, S.; Hiremath, P. B.; Kousalya, Mercy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: There are 3.6 million/year neonatal deaths around the world, of which 99 percent deaths are contributed by the developing countries. An infant born before 37 completed weeks is called as preterm. Normal human pregnancy results in a pronounced physiological hypertriglyceridemia involving a gestational rise in blood triglycerides (TGL) and cholesterol. As elevated circulating levels of triglycerides and cholesterol are markers for increased risk of preterm labor in pregnant women. Atherosis of the Utero placental spiral arteries may be induced by the Hyperlipidemia in pregnancy to cause preterm delivery. Methods: The study group included 444 healthy pregnant women in the age group of 17-35 years and whose gestational age was confirmed either by their last menstrual period or by dating ultrasound. This study was conducted to evaluate the association of elevated serum triglycerides and cholesterol levels, in an uncomplicated pregnancy and preterm delivery. In all these antenatal mothers (study group) a detailed history with special reference to diet and habits, followed by a complete obstetric and general examination were done. All antenatal mothers who were included in the study were subjected for serum triglycerides and cholesterol estimation from the overnight fasting blood samples, at 24, 28, & 32 weeks of gestation. Results: In this study 374 patients who had normal cholesterol delivered at term, however 15 patients out of 26 (42.5%) patients who showed abnormal cholesterol had preterm delivery and 22 patients out of 35 (62.8%) patients with abnormal triglycerides level delivered prematurely. Conclusions: The measurement of serum total cholesterol and triglycerides along with other measures like clinical and serum screening of Alpha fetoprotein and inhibin A can potentially be used for predicting the preterm labor